2013
DOI: 10.1111/1755-0998.12146
|View full text |Cite
|
Sign up to set email alerts
|

Genetic assessment of safflower (Carthamus tinctorius L.) collection with microsatellite markers acquired via pyrosequencing method

Abstract: A genetic evaluation of safflower germplasm collections derived from different geographical regions and countries will provide useful information for sustainable conservation and the utilization of genetic diversity. However, the molecular marker information is limited for evaluation of genetic diversity of safflower germplasm. In this study, we acquired 509 putative genomic SSR markers for sufficient genome coverage using next-generation sequencing methods and characterized thirty polymorphic SSRs in safflowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 40 publications
6
45
4
Order By: Relevance
“…) and safflower (Lee et al . ). High‐throughput molecular genotyping is now also starting to be used in major crops: a recent study used genotyping‐by‐sequencing to characterize lines in the USA national maize inbred seed bank (Romay et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and safflower (Lee et al . ). High‐throughput molecular genotyping is now also starting to be used in major crops: a recent study used genotyping‐by‐sequencing to characterize lines in the USA national maize inbred seed bank (Romay et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Lee et al . ). However, generation of inexpensive high‐throughput molecular marker data is now becoming routine for many genera.…”
Section: Introductionmentioning
confidence: 97%
“…The reproducibility of PCR product size was evaluated by performing three replications using two different samples for each SSR primer. The M13F-tail PCR method of Schuelke (2000) was used to measure the size of PCR products, as described previously (Lee et al, 2014). The PCR master mix was prepared as follows: Each 20 μl reaction mixture contained 20 ng template gDNA, 1X PCR buffer, 2 uM specific primer, 200 uM dNTPs, 4 uM M13 universal primer, 6 uM normal reverse primer, and 0.5 U Taq-polymerase (SolGent, Korea).…”
Section: Genotyping With Microsatellite Markersmentioning
confidence: 99%
“…Application of morphological descriptors and geographical origin to assess the variability of around 2000 lines of safflower revealed a wide range of phenotypic variation for several traits, based on which safflower accessions were classified into 10 "regional gene pools" (Ashri 1975). Several recent studies used molecular markers, viz., random amplified polymorphic DNA (RAPD), inter-simple sequence repeat (ISSR), amplified fragment length polymorphism (AFLP), sequence-related amplified polymorphism (SRAP), and simple sequence repeat (SSR), for variation analysis either exclusively or in conjunction with morphological data for the crop (Sehgal and Raina 2005;Johnson et al 2007;Yang et al 2007;Amini et al 2008;Peng et al 2008;Chapman et al 2009Chapman et al , 2010Khan et al 2009;Mahasi et al 2009;Hamdan et al 2011; Barati and Arzani 2012;Mokhtari et al 2013;Lee et al 2014). However, low sample size from selected regional gene pools and lack of a global representation of available germplasm were limitations in most of these studies, which may therefore not provide an accurate representation of the available genetic diversity and population structure in safflower.…”
Section: Introductionmentioning
confidence: 99%
“…Chapman et al (2010) used 24 EST-SSR markers to survey a representative germplasm collection of 76 accessions belonging to ten centers proposed by Ashri (1975) and redesignated them to five distinct clusters. Recently, Lee et al (2014) proposed three clusters along with few admixture groupings by analyzing 100 safflower accessions from Far East (mainly Korea), India-Pakistan, and Middle East regional gene pools using 30 microsatellite markers. These admixtures indicated that gene flow occurred between gene pools as a consequence of natural selection and human intervention.…”
Section: Introductionmentioning
confidence: 99%